PENGARUH KONTEN TIKTOK TERHADAP TINGKAT PENGETAHUAN TENTANG ANTIBIOTIK PADA MAHASISWA UNIVERSITAS ISLAM INDONESIA - Novi Dwi Rugiarti; Lastri, Lastri; Annisa, Lily (Nusantara Hasana Journal, 2025)
Antibiotic resistance is a global health issue largely caused by the misuse of antibiotics. Increasing public knowledge about rational antibiotic use is a key step in controlling antimicrobial resistance. This study aimed to determine the effect of educational content on the social media platform TikTok on students’ knowledge about antibiotics at Universitas Islam Indonesia. The research employed a pre-test–post-test design, with a 63-second educational video as the intervention. The study involved 351 students selected through accidental sampling. The research instrument was a questionnaire that had been tested for validity and reliability. The results showed a significant increase in the average knowledge score from 73.25% in the pre-test to 91.16% in the post-test (p < 0.05). These findings indicate that TikTok-based educational content effectively improves students’ understanding of appropriate antibiotic use. Social media can serve as an engaging and accessible platform for health education, especially among young people. Utilizing TikTok as a medium for health promotion is expected to support national efforts in preventing antimicrobial resistance in Indonesia.